Editorial: interventions in infantile colic – can efficacy be attributed to treatment or to time? Authors' reply. Issue 3 (14th January 2020) - Nocerino, Rita; De Filippis, Francesca; Cecere, Gaetano; Marino, Antonio; Micillo, Maria; Di Scala, Carmen; de Caro, Carmen; Calignano, Antonio; Bruno, Cristina; Paparo, Lorella; Iannicelli, Anna Maria; Cosenza, Linda; et al.
Abstract : LINKED CONTENT This article is linked to Nocerino et al and Iacovou papers. To view these articles, visit https://doi.org/10.1111/apt.15561 and https://doi.org/10.1111/apt.15599 .